The anti-leprosy campaign in Colombia: the rhetoric of hygiene and science, 1920-1940 - Diana Obregón (História, Ciências, Saúde: Manguinhos)
Since the 1920s, the medical community realized that the strategy of leprosy control based on segregation and persecution of patients was inefficient and expensive. In the 1930s the new liberal government incorporated leprosy within the general sanitary institutions, by merging the Bureau of Lazarettos and the National Department of Hygiene. The disease-apart approach started to be replaced by a more general public health strategy, which involved controlling other illnesses. Prevention and research played a more influential role, and the new sanitary officials saw leprosy in the light of the economic rationality of expenditures, placing more emphasis on therapies and making them mandatory for all patients. Improvements in leprosy treatment became widely known and available. However, the image of leprosy as a special condition and the practice of segregation were deeply entrenched within the Colombian culture and institutions. The rhetoric changed, but to break with several decades of persecution was a difficult task